INVENTARISASI ANGGREK TERESTIAL DI HUTAN PENDIDIKAN KAWASAN TAMAN HUTAN RAYA BUKIT BARISAN TONGKOH KABUPATEN KARO SUMATERA UTARA - Ulinar Amantha Pasaribu; Pindi Patana; Yunasfi Yunasfi (Program studi Kehutanan USU, 2015)
Indonesia is a country which has the biggest wealth of orchid in the world. Indonesia has about 6.000 types of orchid in the world. In approximately 26.000 types of orchid, about 90% of the dendrobium stem species which are developed in the world are from Indonesia. This study aims to inventory the species of orchid which were found inthe Forest Education TAHURA Bukit Barisan Tongkoh Karo. Determination of the observation locationswhich were conducted by using purposive sampling method. The data which were collected in this study were: the types of orchid, elevation, position point, soil pH, temperature and humidity, and then the identification and analysis of vegetation types. The results of this study indicated that orchids which were found in the Forest Education TAHURA Bukit Barisan Tongkoh Karo were 13 species of terrestrial orchids which consists of 8 genus. The highest INP value was 35.613 % on the type of Calanthe sp. and the lowest was 4.772 % on the type of Liparis sp. Diversity index H ' was 2.0. The most dominant genus of orchid was the type of the Calanthe genus which was Calanthe sp. which amounts to 69 individuals and the type of the Phaius genus which was Phaius sp. which amounts to 64 individuals.Keywords: terrestrial orchids, inventory, educational forest, Education Forest, TAHURA Bukit Barisan